t(4-1)+9=27

Simple and best practice solution for t(4-1)+9=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t(4-1)+9=27 equation:


Simplifying
t(4 + -1) + 9 = 27

Combine like terms: 4 + -1 = 3
t(3) + 9 = 27

Reorder the terms for easier multiplication:
3t + 9 = 27

Reorder the terms:
9 + 3t = 27

Solving
9 + 3t = 27

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 3t = 27 + -9

Combine like terms: 9 + -9 = 0
0 + 3t = 27 + -9
3t = 27 + -9

Combine like terms: 27 + -9 = 18
3t = 18

Divide each side by '3'.
t = 6

Simplifying
t = 6

See similar equations:

| 5(2+3w)-1=-6 | | 5(2z-1)-4(z+3)=4(z+1) | | 6(6+6v)=36-v | | (2+3w)-1=-6 | | 6y=5 | | (x+2)(x-2)=1 | | -28=196x | | 80000-2x=x | | -6x+4x=-12 | | 8.69=-1-4.7x-x | | 5(2z-1)-4(2+3)=4(2+1) | | 4x=-1+2(x+1) | | 14-(x+5)=4x-6 | | 8-5x=x-16 | | 2(x+3)-5[4-(x-6)]=x+2 | | 4+9=-8+-13 | | 2x+8y=24 | | 4y-6=-2y-11 | | xsuared=x-6 | | -2(5n+2)=4 | | -2.25=-2.6x+0.16 | | g/10+14=5 | | 3(5a-4)= | | 4(3.14)=w-6(3.14) | | 8+3t=4 | | 4x+2y=250 | | 9.5=3.6n+1+2n | | x=190 | | 5(a+4)-4(a+3)=0 | | -3-x=-15 | | 4=1-n+2 | | 14x-4+12x=1x |

Equations solver categories